Fish technology : (Spinger, 2002)
Fluorescence in situ hybridization (FISH) is a procedure which allows the direct visualization localization of genomic alterations. The technique has been adapted to a wide range of applications in both medicine, especially diagnostic cytogenetics and biology. This book looks at FISH technology.